Pertussin 30—Preventive for whooping cough? - English, J.M. (British Homeopathic Journal, 1987)
The primary purpose of this study was to be a pilot for a further, larger study to determine whether the homœopathic preparation Pertussin 30c was effective in preventing whooping cough. It was recognized that neither the numbers involved, nor the method followed would of themselves be sufficient to prove efficacy, but it was hoped that a positive result would permit the conclusion to be drawn that a further study would be in the public interest.694 valid replies from 1100 questionnaires sent to the parents of children who had had Pertussin 30 were compared with Hillingdon District's notified figures. Hillingdon FPC provided evidence of a wide degree of variability in the notification rates of pertussis. When there were taken into account the result suggested a degree of activity for Pertissin in excess of 50%. Although the assumptions are reasonable in themselves, no claim can be made to have demonstrated the effect of Pertussin in a statistially valid way. It is reasonable, however, to conclude that there is a good technical case for further investigation to be undertake, although with rising immunization rates it may not be justified in terms of reward for its cost. The trial has helped to define a possible method for doing this, which is described.